An open‐label, randomized crossover study to evaluate the acceptability and preference for contraceptive options in female adolescents, 15 to 19 years of age in Cape Town, as a proxy for HIV prevention methods (UChoose). Issue 10 (9th October 2020) - Gill, Katherine; Happel, Anna‐Ursula; Pidwell, Tanya; Mendelsohn, Andrea; Duyver, Menna; Johnson, Leigh; Meyer, Landon; Slack, Catherine; Strode, Ann; Mendel, Eve; Fynn, Lauren; Wallace, Melissa; et al.
Abstract: Introduction: Young women in Southern Africa have extremely high HIV incidence rates necessitating the availability of female‐controlled prevention methods. Understanding adolescent preference for seeking contraception would improve our understanding of acceptability, feasibility and adherence to similar modes of delivery for HIV prevention. Methods: UChoose was an open‐label randomized crossover study over 32 weeks which aimed to evaluate the acceptability and preference for contraceptive options in healthy, HIV‐uninfected, female adolescents aged 15 to 19 years, as a proxy for similar HIV prevention methods. Participants were assigned to a contraceptive method for a period of 16 weeks in the form of a bi‐monthly injectable contraceptive, monthly vaginal Nuvaring ® or daily combined oral contraceptive (COC) and then asked to state their preference. At 16 weeks, participants crossed over to another contraceptive method, to ensure that all participants tried the Nuvaring ® (least familiar modality) and additionally, either the injection or COC. Primary outcomes were contraceptive acceptability and preference. At the end of the 32 weeks they were also asked to imagine their preference for an HIV prevention modality. Secondary endpoints included changes in sexual behaviour, contraceptive adherence and preference for biomedical and behavioural HIV prevention methods. Results: Of the 180 participants screened, 130 were enrolled and randomized to the Nuvaring ® (n = 45), injection (n = 45) or COC (n = 40). Significantly more Nuvaring ® users (24/116; 20.7%) requested to change to another contraceptive option compared to injection (1/73; 1.4% p  = 0.0002) and COC users (4/49; 8% p  = 0.074). Of those that remained on the Nuvaring ®, adherence was significantly higher than to COC ( p  < 0.0001). Significantly more injection users (77/80; 96.3%) thought this delivery mode was convenient to use compared to Nuvaring ® (74/89; 83.1%; p  = 0.0409) or COC (38/50; 76.0%; p  = 0.0034). Overall, the preferred contraceptive choice was injection, followed by the ring and lastly the pill. Conclusions: Adherence to daily COC was difficult for adolescents in this cohort and the least favoured potential HIV prevention option. While some preferred vaginal ring use, these data suggest that long‐acting injectables would be the preferred prevention method for adolescent girls and young women. This study highlights the need for additional options for HIV prevention in youth.